2021
DOI: 10.2147/opth.s302757
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Detachment After Endophthalmitis: Risk Factors and Outcomes

Abstract: Purpose To analyze the risk factors, clinical course, and visual and anatomic outcomes of retinal detachment (RD) after endophthalmitis. Patients and Methods This retrospective study included 108 patients diagnosed with endophthalmitis between August 2014 and May 2019 at a single tertiary referral center. Sixteen patients developed RD after endophthalmitis. Retrospective analysis was performed to compare the cohort of endophthalmitis alone versus the cohort that develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 25 publications
1
20
1
Order By: Relevance
“…5 Chiquet et al, Wang et al, and Lee et al also did not report any relationship between organisms and RD rates. 6,11,20 In this review, 21 (66%) of the RD cases occurred within the first month after endophthalmitis diagnosis. This is comparable with the 56% in the investigation of Chiquet et al The rate of RD managed surgically was 94%, similar to that in Chiquet et al (93%) yet higher than in EVS (44%).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…5 Chiquet et al, Wang et al, and Lee et al also did not report any relationship between organisms and RD rates. 6,11,20 In this review, 21 (66%) of the RD cases occurred within the first month after endophthalmitis diagnosis. This is comparable with the 56% in the investigation of Chiquet et al The rate of RD managed surgically was 94%, similar to that in Chiquet et al (93%) yet higher than in EVS (44%).…”
Section: Discussionmentioning
confidence: 82%
“…5 Chiquet et al, Wang et al, and Lee et al also did not report any relationship between organisms and RD rates. 6,11,20…”
Section: Discussionmentioning
confidence: 99%
“…The rate of RRD at presentation including development of RRD within 14 days after initial presentation were 8 patients (9 eyes, 22.5%). From previous reports, rate of RRD in endogenous endophthalmitis varied from 4.9% to 26.67% 4 , 15 18 . Virulence of organism and diabetes were previously reported as possible risk factors of developing RRD in exogenous endophthalmitis 19 , 20 .…”
Section: Discussionmentioning
confidence: 87%
“…Wang et al . reported that aphakia and presence of posterior synechiae were associated with the development of RD, but they included both exogenous and endogenous endophthalmitis in their study 15 . In our study, 7 of 16 eyes (43.75%) which developed RRD had hypopyon at presentation and 6 of 15 patients (40%) had diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In the late phase, contractile membranes may form on the surface of the retina. Both retinal necrosis and membrane proliferation can produce multiple retinal breaks and defects that may lead to retinal detachment [ 31 , 32 ]. A similar process occurs in acute retinal necrosis, in which retinal detachment has been described in up to 75% of eyes within 3 months of the onset of symptoms [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%